Vibrações induzidas por multidões: efeito nos movimentos corpóreos dos pedestres na direção transversal - Silva, Felipe Feliciano Gomes da (2016)
The analysis of the vibrations induced by crowds in the transverse direction has become a topic of increasing interest, because of the ocurrence of excessive transverse vibrations in certain structures due to pedestrian traffic. This work presents the analysis of movements of pedestrians in the transverse direction for crowd situations. Successive tests were carried out with persons instrumented, walking alone and in a crowd. Comparisons between measurements of these pedestrians walking alone and in the crowd provided the identification of the influence of the crowd in the transverse acceleration and displacements and rotation of the pelvis.